2020
DOI: 10.3390/ijerph17010333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar Application on Soil Organic Carbon Composition and Enzyme Activity in Paddy Soil under Water-Saving Irrigation

Abstract: Rice water-saving irrigation technology can remarkably reduce irrigation water input and maintain high yield; however, this technology can also accelerate the decomposition of soil organic matter in paddy fields. The spatial and temporal distributions of soil organic carbon (SOC), water-soluble organic carbon (WSOC), and soil microbial biomass carbon (SMBC) under different water-carbon regulation scenarios were analyzed on the basis of field experiments in the Taihu Lake region in China to explore the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 38 publications
11
28
0
2
Order By: Relevance
“…Biochar surface has numerous pores that provide shelter to microbes against stress [75], which results in an increase in SMB. Similar findings were also observed in the previous studies which reported an increase in SMBC due to biochar application [76][77][78]. However, in contrast, no change in MBC under biochar application was observed by Bruun et al [73].…”
Section: Effect Of Organic Amendments On Smb and Enzyme Activitysupporting
confidence: 90%
“…Biochar surface has numerous pores that provide shelter to microbes against stress [75], which results in an increase in SMB. Similar findings were also observed in the previous studies which reported an increase in SMBC due to biochar application [76][77][78]. However, in contrast, no change in MBC under biochar application was observed by Bruun et al [73].…”
Section: Effect Of Organic Amendments On Smb and Enzyme Activitysupporting
confidence: 90%
“…The SOC concentration at the 0–10 cm soil depth before sowing was significantly larger under STF and NTF than under PTF ( P < 0.05) and was similar to the results reported by previous researchers [ 38 , 39 ]. The lower SOC concentration in our study under PTF might have been due to a large volume of crop residues being turned into the deeper layer (25–30 cm) through the summer tillage practice.…”
Section: Discussionsupporting
confidence: 91%
“…Wang et al [117] found that, although returning rice straw was an effective practice to increase SOC in the short-term, it might not have effects in the long-term. Meanwhile, biochar application is recommended from various studies (e.g., rice straw biochar for paddy soil [118] because it is more resistant to microbial decomposition unless management practices change. In cultivated sandy soil like paddy field in NE Thailand, SOC is often lost due to tillage, crop residue removal, and fallow land after harvest; as a result, SOC is lower than the maximum protective capacity level.…”
Section: Carbon Saturation For Sandy Soil In Northeast Thailandmentioning
confidence: 99%